2008
DOI: 10.1016/j.lmot.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization and habituation of motivated behavior in overweight and non-overweight children

Abstract: The rate of habituation to food is inversely related to energy intake, and overweight children may habituate slower to food and consume more energy. This study compared patterns of sensitization, as defined by an initial increase in operant or motivated responding for food, and habituation, defined by gradual reduction in responding, for macaroni and cheese and pizza in overweight and nonoverweight 8−12 year-old children. Non-overweight children habituated faster to both foods than overweight children (p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…Previous studies have shown that there is a slower habituation to a taste stimulus in obese participants as compared with lean ones, 54 as well as a greater effect of sensitization on responding for food in overweight versus non-overweight children. 55 Therefore, it is possible that the overweight participants were sensitized by the unbiased viewing condition and therefore showed an elevated response during taste imagination, whereas the healthy-weight were habituated after unbiased viewing and therefore showed a decreased response during Ambivalent reward activity in overweight women A Frankort et al , hunger sensations may have differed between groups during the taste imagination condition, although they were similar at the start of the scanning session. Increased hunger in the overweight group could thus have led to the elevated response during taste imagination in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is a slower habituation to a taste stimulus in obese participants as compared with lean ones, 54 as well as a greater effect of sensitization on responding for food in overweight versus non-overweight children. 55 Therefore, it is possible that the overweight participants were sensitized by the unbiased viewing condition and therefore showed an elevated response during taste imagination, whereas the healthy-weight were habituated after unbiased viewing and therefore showed a decreased response during Ambivalent reward activity in overweight women A Frankort et al , hunger sensations may have differed between groups during the taste imagination condition, although they were similar at the start of the scanning session. Increased hunger in the overweight group could thus have led to the elevated response during taste imagination in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Finding heightened salivary reactivity in overweight individuals is consistent with previous research demonstrating that overweight adults and children are slower to achieve salivary habituation after repeated exposure to a food cue. 20,21,25 In relation to energy intake, food-cue exposure can have two consequences; it can prime an individual to engage in eating behavior and it can increase the amount of food that is selected and subsequently consumed. 7 We found overweight/lean differences only in the former.…”
Section: Discussionmentioning
confidence: 99%
“…Also, overweight children are slower to show salivary habituation after repeated exposure to a food cue. 20,21 In adults, obese individuals salivate more in response to a food cue and are slower to develop salivary habituation. [22][23][24][25] However, these findings might otherwise be explained by differences in dietary restraint, [26][27][28][29][30] which is correlated with body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of habituation to food is related to food consumption, because slower rates of habituation are associated with greater energy intake (4)(5)(6). The rate of habituation within an eating session differs between obese and lean subjects, with obese subjects habituating at a slower rate than leaner subjects (5,7,8). The rate of habituation also predicts weight gain in children, because those who habituate slower show greater gains in BMI z scores than do those who habituate at a faster rate (9).…”
Section: Introductionmentioning
confidence: 99%
“…Obese adults (7,13) or overweight children (5,8) habituate at slower rates to repeated food stimuli than do leaner subjects.…”
Section: Introductionmentioning
confidence: 99%